Speech recognition thresholds in-quiet and in-noise and its relationship with aided thresholds in post-lingual adult cochlear implant users in Malaysia - Salahuddin, Nur Baizura (2023)
Introduction: Testing speech perception is a crucial part of tracking performances of cochlear implant (CI) users however it is not routinely performed in Malaysia because of limited access to speech tests. This study examines the speech recognition thresholds (SRT) of CI users using one in-quiet and two in-noise speech tests: 1) Bisyllabic Malay Speech Audiometry (BMSA), 2) Malay Matrix Sentence Test (MMST), and 3) Malay Digit Triplet Tests (MDTT). Their relationship with pure-tone audiometry aided thresholds (PTAAT) were also investigated. Methods: In this cross-sectional study, SRT measurements for all three speech tests were collected from 22 experienced (average device age of 4.7 ± 3.7 years) post-lingual adult CI users. Participants had a median age of 39 years old (IQR = 33 to 34) and PTAAT of 34 dB HL (IQR = 34 to 36). Results: Median SRT of BMSA, MMST and MDTT were 45 dB SPL (IQR = 43.2 to 53.5), -3.2 dB SNR (IQR = -5.5 to -0.2), and -1.8 dB SNR (IQR = -3.9 to -1.6), respectively. Spearmen’s rank-order correlation revealed no statistically significant correlations between average PTAAT and the SRT of BMSA (rs(22) = .312, p = .18), MMST (rs(22) = .081, p = .74) and MDTT (rs(22) = .125, p = .6). Conclusion: SRT performance are predictably good in quiet but poor in background noise. PTAAT is a poor estimator of speech perception abilities. Speech tests should be routinely performed pre- and post- CI use as PTAAT is not a reliable measure of speech-sounds accessibility.